ANALISIS ANGKA KUMAN UDARA DI RUANG PERAWATAN KELAS III RUMAH SAKIT DKT KOTA BENGKULU - Febriani, Delly (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Air is one important element in the life of living creatures of the earth and a gas mixturecontained in a layer that surrounds the Earth . Air can also act as a means of nosocomial infection .Classrooms III which is the room most at risk of nosocomial infections , where one room within thebed did not qualify and the officer did not use personal protective equipment. The research objectivewas to determine the total number of bacteria in the treatment room air class III special room 1 maleand 2 women’s rooms in room sick DKT Bengkulu city. This type of research is qualitativedescriptive approach a study that describes the number of total number of bacteria in the air in a ClassIII hospital treatment DKT city of Bengkulu. Based on the results of the study the total number of airgerms in the classroom III consists of one room for boys is 511 CFU /m3 and women’s room 2 is 556CFU / m3 . Personal hyigene expected increase for staff and visitors to wash their hands obedientlybefore and after the entrance of the room.